Analisis Pengukuran Kualitas Hasil Pengecoran Bilah Gangsa Gamelan Dengan Metode Six Sigma - Marcelo, Briyan; Priambadi, I Gusti Ngurah; Dewi, A.A.A.I.S. Komala (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
aAbstracttt The motivation for this study is that competition in the gamelan market continues to grow, and people's views are changing from price to quality. The quality of Gamelan castings iskakfactorkthatkmustkbekconsideredkin the manufacturing process. The purpose of this research is to use the Six Sigma method to reduce the quality defect level of gamelan castings. The Six Sigma equipment used is DMAIC (definition, measurement, analysis, improvement, control). This research was conducted using an experimental method that uses Six Sigma rules to test to obtain or determine geometric defects in castings. The research object is 41 Bali Gamelan Pemmade Sutama bars, the mixing ratio of the material is 80% Cu - 20% Sn. Research data is obtained through direct observation, literature search, and records. The software used in this study is Statistical Products and Service Solutions (SPSS). The results showed that of the 41 gamelan sheets manufactured, 17 defects appeared. It can be seen that the sigma launch quality level of Bali gamelan is 1.7253. The quality results of Pemmade Sutama's Bali gamelan castings are quite good, but material failures often occur, which can cause considerable losses if not handled, because more and more products are not qualified during the casting process production, which, of course also increases production costs. Keywords: Gamelan Bars, Six Sigma, Casting, Quality Results, Casting Defects